Influence of Dynamic Loading on Fracture Behaviour of DCB Sandwich Specimen - Burlayenko, V. N.; Sadowski, Tomasz; Pietras, D. (My University, 2019)
Numerical simulations of dynamic fracture behaviour of a double cantilever sandwich beam subjected to uneven bending moments in plane conditions are carried out using the dynamic finite element analyses with the ABAQUSTM code. The strain energy release rate was evaluated by means of the finite element model developed within the two-dimensional (2-D) linear elastodynamic theory. This demonstrates the capability and the reliability of the finite element modelling as an extremely useful numerical tool for solving dynamic fracture mechanics problems. Also, the dynamic behaviour of fracture parameters and interface crack progression is discussed.
Keywords: numerical simulations; dynamic fracture behaviour; finite element method; sandwich materials; cohesive finite elements